Using interactive teaching methods in economic education: a problematic aspect - ZURAVSKA, Nina; YAKOVENKO, Olena (Journal of Education, Technology and Computer Science, 2013)
The article emphasizes the modern demands of training of competent specialists.It is proposed to solve this problem by using interactive teaching methods,such as the most appropriate for the ultimate aim of education. Classificationof such methods is done. It’s emphasized on the problems of their application,analyzed of the main aspects of their poor using in economic education.Suggestions for better implementation of interactive teaching methods in vocationaleducation are done.